Answer:
![y^2-(7)/(2)y+3](https://img.qammunity.org/2022/formulas/mathematics/high-school/e3qtp6clgnk3ru3rgjhgagz2n85krfhimj.png)
Explanation:
Given polynomial is,
6y² - 7y - 2
Fro the zeros of the given polynomial,
6y² - 7y - 2 = 0
6y² - 4y - 3y - 2 = 0
2y(3y - 2) - 1(3y - 2) = 0
(2y - 1)(3y - 2) = 0
(2y - 1) = 0
y =
![(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/f0qcv9cek84ihznc3s7uf39dlk9xfru67q.png)
(3y - 2) = 0
y =
![(2)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9l76ru6jxv4fv4b8lpmxx1u47fxut8ydly.png)
Therefore, zeros of this polynomial are m =
and n =
![(2)/(3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9l76ru6jxv4fv4b8lpmxx1u47fxut8ydly.png)
If a polynomial has zeros as
and
then the zeros will be
and 2.
Polynomial will be,
![(y-(3)/(2))(y-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/heae50q13oe6zzihj5f3krpffraiz5gk82.png)
=
![y(y-2)-(3)/(2)(y-2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/rkf1xjn8cbf4sydknb327dbhgfe00yhcdw.png)
=
![y^2-2y-(3)/(2)y+3](https://img.qammunity.org/2022/formulas/mathematics/high-school/sxa2j3tygccilvsbvhhx199ki3okabn7ft.png)
=
![y^2-(7)/(2)y+3](https://img.qammunity.org/2022/formulas/mathematics/high-school/e3qtp6clgnk3ru3rgjhgagz2n85krfhimj.png)